An Overview of Anticancer Chalcones with Apoptosis Inducing Activity - Hassan Mirzaei; Masoud Keighobadi; Saeed Emami (Journal of Mazandaran University of Medical Sciences, 2017)
Cancer is a complex and life-threatening disease involving uncontrollable cell proliferation, evading apoptosis, and metastasis. Despite recent developments in cancer chemotherapy, there are no effective broad spectrum anticancer agents that could selectively target cancer cells. Thus, designing and discovering new efficient and selective anticancer agents are urgent needs. It is important that new anticancer agents could act via apoptosis induction, since it has a critical role in control of cell proliferation. Chalcones are naturally occurring compounds possessing high degree of synthetic diversity for design of new leading bioactive compounds including anticancer agents. Chalcones are considered as promising anticancer agents against most human cancers with capability of inducing apoptosis in cancer cells. Furthermore, some clinically useful anticancer drugs show genotoxicity due to interaction with DNA, but chalcones with different mechanism may be devoid of this side effect. This review highlights the recently identified anticancer chalcones from naturally or synthetically origins that induce apoptosis in cancer cells. The diversity of scaffolds described in this review along with their structure-activity relationships could help medicinal chemists in development of new selective anticancer chalcones with improved potency.